Analysis of Morphologic and Rheological Properties of Hyaluronic Acid Gel Fillers to Body Contouring and Its Clinical Correlation - Maria Cláudia Almeida Issa; Renata M. M. Viana; Paulo R. de Souza Mendes; Mônica F. Naccache; Priscila R. Varges; Eliana P. Marín Castaño; Eliandre Palermo (Gels)
The demand for minimally invasive body contouring procedures, particularly for gluteal augmentation, has grown significantly. This study evaluates the morphologic and rheological properties of four commercially available hyaluronic acid (HA) fillers used for body contouring and explores their clinical implications. Critical parameters such as storage modulus (G′), loss modulus (G″), complex modulus (G*), and damping factor (tan δ) were measured using oscillatory rheological tests to assess each filler’s elasticity, viscosity, and viscoelastic profile. Scanning Electron Microscopy (SEM) was performed to analyze the microstructure of the fillers, providing insights into their microscopic architecture. The results showed differences in mechanical properties and viscoelastic behavior among the fillers. These variations suggest that the choice of filler may need to be tailored to specific body contouring requirements. Understanding these differences is crucial for achieving the best clinical results and patient satisfaction, helping professionals select the most suitable filler for each case.